The Effects Of Extensive Reading Activites On Students Vocabulary Mastery At SMA Islam Raudatul Ulum Batu Jangkih In The Academic Year 2024/2025 - Zakrah, Siti; Herman; Hasbullah; Aristiawan, Danul (P@RAD!GMA : Jurnal Kajian Budaya & Media, 2024)
This study aims to identify the impact of extensive reading activities on students' vocabulary mastery at SMA Islam Raudatul Ulum Batu Jangkih during the 2024/2025 academic year. The research employs a quantitative approach with a pre-experimental design. The sample consists of 33 eleventh-grade students, including 18 females and 15 males. The instruments used for data collection were pre-tests and post-tests, designed to assess students' vocabulary skills before and after the intervention through extensive reading activities tailored to their proficiency level. The students participated in extensive reading sessions over four meetings, with reading materials chosen according to their interests and abilities. After the intervention, the data were analyzed using a paired sample t-test with the assistance of SPSS version 20 to determine the effectiveness of the method. The results showed a significant improvement in students' vocabulary mastery after engaging in extensive reading activities. The average pre-test score was 56.81, while the post-test average increased to 78.33. The t-test results indicated a significant value (p-value) of 0.001, demonstrating a significant difference between pre-test and post-test scores, indicating that the extensive reading method had a positive impact. These findings suggest that the extensive reading model is not only effective in improving students' vocabulary mastery but also in increasing their motivation to read independently. Therefore, English teachers are encouraged to integrate extensive reading into their teaching methods to enhance vocabulary acquisition and other language skills such as comprehension and speaking.